Preliminary spectrum of genetic variants in familial hypercholesterolemia in Argentina - Bañares, Virginia (2017)
Fil: Bañares, Virginia G. ANLIS Dr.C.G.Malbrán. Centro Nacional de Genética Médica; Argentina. Departamento de Genética Experimental; Argentina.